Effects of Sedentary Behavior and Fast-Food Consumption Habit on Body Mass Index Among Obese Children In Siwalankerto Village, Surabaya - Desta Ayu Cahya Rosyida; Setiawandari Setiawandari (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
Obesity is the basis of various non-communicable diseases such as diabetes, hypertension, and cardiovascular diseases, which are currently major health problems in Indonesia. Furthermore, other consequences that may arise are a greater risk of social and psychological problems such as stigmatization and low self-confidence. Hence, researchers expect to change the pattern of sedentary behavior and the fast-food consumption habit among obese children. This research was a quantitative study. The treatments were applied towards two groups, and the conditions before and after treatment were compared. The results revealed that the mean Body Mass Index (BMI) among children in the sedentary behavior group before and after the intervention were 28.2 (Obesity I) and 19.2 (Normal BMI), respectively. Meanwhile, the mean BMI in the fast-food consumption habit group before and after the intervention were 28.2 (Obesity I) and 20.5 (normal BMI), respectively. The statistical analysis showed a significant difference in the decrease in BMI between the two groups (p<0.05). The sedentary behavior group showed a higher mean value than the fast-food habit group, namely 20.0 and 19.6, respectively. Thus, it can be concluded that the intervention in the sedentary behavior group was more influential than the fast-food habit group.